The Role of Financial Markets in Energy Transitions - Magdalena Zioło; Iwona Bąk; Anna Spoz (Energies)
This review organizes the current state of knowledge on the role of financial markets in energy transition. The originality of the study lies in the delimitation of its scope and diagnosis of research trends concerning the role of financing, innovation, and financial development sources. The study sets out to identify the role of the financial market in the energy transition process and present the state-of-the-art and main research focuses. For this purpose, a literature review was carried out based on the search results from the Web of Science database and using VOSViewer software, version 1.6.20. The analysis of 54 papers in the final sample allowed us to pinpoint the key links between financial markets and energy transition. Capital markets support green initiatives, with green bonds as a primary funding source. Blockchain and fintech technologies also significantly contribute to transition by offering innovative solutions. Additionally, a range of papers examine the costs associated with energy transition and the role of financial instruments in managing these. Regulatory challenges are another significant focus. This comprehensive analysis underscores the multifaceted relationship between financial markets and energy transition, providing insights into the current trends and the critical role of finance in fostering a sustainable future.